Ultrafast Charge and Long Life of High‐Voltage Cathodes for Dual‐Ion Batteries via a Bifunctional Interphase Nanolayer on Graphite Particles. Issue 12 (1st January 2023) - Zhang, Kejia; Li, Decheng; Shao, Jie; Jiang, Yu; Lv, Linze; Shi, Qiang; Qu, Qunting; Zheng, Honghe
Abstract: Dual‐ion batteries (DIBs) with Co/Ni‐free cathodes especially graphite cathodes are very attractive energy storage systems in the long run because of the cost effectiveness and sustainability. However, graphite cathodes severely suffer from poor structural stability during anions storage at high potentials owing to the oxidative decomposition of electrolytes and volume expansion. This work proposes an artificial cathode/electrolyte interphase (CEI) strategy by implanting polyphosphoric acid (PPA) nanofilms tightly on natural graphite (NG) particles via interfacial hydrogen bonding. The electrochemical results show that the PPA‐modified graphite cathodes possess enhanced charge–discharge reversibility, accelerated electrode reaction kinetic, decreased resistance, decelerated self‐discharge, and prolonged cycling life. Through post‐analyses on the cycled graphite cathodes, the improved performance is mainly attributed to the PPA‐based CEI, which effectively mitigates the electrolyte decomposition and protects the graphitic structure. More interestingly, the hydrogen bonding interactions between poly(vinyldifluoride) (PVDF) binder and PPA as validated through density functional theory calculations and practical experiments can increase the contact sites of PVDF chains on NG@PPA particles. Meanwhile, the cross‐linking effect of PPA can enhance the mechanical strength of PVDF, thus the long life of NG@PPA cathode is also correlated with the improved mechanical stability of the entire electrode. Abstract : A bifunctional nanolayer uniformly implanted on graphite particles not only contributes to the formation of a thin, smooth and flexible cathode/electrolyte interphase, which mitigates the electrolyte decomposition and protects the layered graphite from structural degradation upon anions insertion/extraction at high‐voltage, but also enhances the mechanical strength and cycling‐life of graphite cathodes through interfacial hydrogen bonding interactions.